5a-(1+3a)=2a-1

Simple and best practice solution for 5a-(1+3a)=2a-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a-(1+3a)=2a-1 equation:


Simplifying
5a + -1(1 + 3a) = 2a + -1
5a + (1 * -1 + 3a * -1) = 2a + -1
5a + (-1 + -3a) = 2a + -1

Reorder the terms:
-1 + 5a + -3a = 2a + -1

Combine like terms: 5a + -3a = 2a
-1 + 2a = 2a + -1

Reorder the terms:
-1 + 2a = -1 + 2a

Add '1' to each side of the equation.
-1 + 1 + 2a = -1 + 1 + 2a

Combine like terms: -1 + 1 = 0
0 + 2a = -1 + 1 + 2a
2a = -1 + 1 + 2a

Combine like terms: -1 + 1 = 0
2a = 0 + 2a
2a = 2a

Add '-2a' to each side of the equation.
2a + -2a = 2a + -2a

Combine like terms: 2a + -2a = 0
0 = 2a + -2a

Combine like terms: 2a + -2a = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 6y-15=-7y-2y | | 8+2m-6=7m+5-2m | | 3x/5=3/20 | | 3a+8b=9 | | 6g-3g-12=g-20 | | 2x-37=17 | | 2z=z+47 | | 40x+x^2=329 | | 17+n=3n-5 | | -(2m+2)-5(m-1)= | | 5a-(1+3a)=26+5a | | t+58=3t | | 11+q=5 | | 4B+4B-5=11 | | 9c-6-(c+3)= | | 11+9=5 | | 4x+(5)+a=50 | | 0=3x^2-30x+48 | | an=2n-9 | | 3-x/8=-3 | | X=sinh^2(1-t) | | 2(x-3)+5=3(w-1) | | 45+2y-x=0 | | -4/9=y-1/12 | | 9(90-x)=180 | | 200+35w=800 | | 8(a+7)-1=87 | | .75(6)^(x)=4(1/3)^(x) | | 31+4m=-5(m+1) | | 15+(2l)+l=72 | | 4v-7=-2v+6v | | v^2+27v+189=0 |

Equations solver categories